Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Ammonium persulfate activated DMSO as a one-carbon synthon for the synthesis of methylenebisamides and other applications - Mahajan, Pankaj S.; Tanpure, Subhash D.; More, Namita A.; Gajbhiye, Jayant M.; Mhaske, Santosh B. (RSC Advances, 2015)
Activation of DMSO to work as an economical and environmentally benign one-carbon synthon has been achieved by using a bench-top reagent ammonium persulfate for general and efficient access to symmetrical methylenebisamides from primary amides. This methodology was used to achieve a three-component Mannich reaction using acetophenone, saccharin and DMSO to furnish a beta-amino ketone. It also provided a metal-free synthesis of thiadiazole and bis(phenyl)methane. Effectively, this method uses DMSO as a safer surrogate to formaldehyde. A mechanism for methylenebisamide formation involving radical intermediates has been proposed based on mechanistic studies.

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.

Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Achmatowicz reaction: A versatile tool in bioactive natural products synthesis - Mahajan, Pankaj S.; Humne, Vivek T.; Mhaske, Santosh B. (Current Organic Chemistry, 2017)
Achmatowicz reaction has emerged as an efficient tool in organic synthesis since its discovery in 1971 by Achmatowicz Jr. The original protocol went through several advantageous variations. Biocatalytic and metal catalyzed versions of this reaction are some of the significant achievements, which further enhanced its effectiveness. The pyranone product of the Achmatowicz reaction is a versatile building block for the synthesis of bioactive scaffolds, drugs and natural products. The present review covers the application of the Achmatowicz reaction in the synthesis of natural products and bioactive molecules reported from 1971 to date. It has been divided into seven sections on the basis of the core structures of the natural products synthesized utilizing the Achmatowicz reaction. We believe that this comprehensive review will attract many more organic chemists to explore its utility in organic synthesis, especially in the synthesis of bioactive natural products as well as drugs in their efficient and atom economical synthesis.
Keywords: Achmatowicz reaction; carbohydrates; Furanols; Natural products; pyranones; Total synthesis

Silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization (C sp3 –C sp2 ) via memory of chirality: access to circumdatin alkaloids - Mahajan, Pankaj S.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization has been developed to form a Csp3–Csp2 bond via memory of chirality. The application of the process has been demonstrated for the synthesis of the circumdatin class of alkaloids in high enantiopurity with retention of the configuration. The developed protocol is mild and works with an inexpensive silver catalyst in the absence of ligand, base, or additives. The involvement of a monoradical in the reaction has been established by trapping the radical intermediate.